An Analysis of the Importance and Conservation of Adobe Material in the Traditional Architecture of Elazığ - Akyıldız, Nihal Arda; Şahin, Murat (Ankara Üniversitesi, 2025)
Abstract In recent years, the construction industry has created serious threats worldwide due to the ecological damage caused by issues such as global warming and waste management resulting from the energy consumed in the production and use of building materials. In this context, renewable energy sources and materials that support ecology and reduce environmental problems have gained increasing importance. Consequently, numerous scientific studies and applications have been carried out in the construction industry on the use of ecological materials and nature-friendly construction systems. Interest in traditional architectural criteria, construction techniques, and materials has also increased due to their noteworthy solutions in recent times. Earth-based adobe material, one of the building materials of traditional architecture, and its unique construction technique have also become a highly noteworthy topic in the field of ecological architecture in recent times. The low energy consumption in the production of earth-based adobe material, its compatibility with environmentally friendly construction techniques in application areas, along with its features supporting waste management and user comfort, have made it more appealing in the field of architecture. The study focuses on the extent to which the approach to preserving traditional architecture in rural/urban settlement areas in Elazığ is rationalist in terms of building/settlement scale, with reference to the contributions that mudbrick structures can make to preservation and ecological urban development. In this sense, the study aims to highlight the importance of transferring traditional settlement areas to the future with their unique elements and socio-cultural values through conservation interventions at the building and settlement scale. The study will reveal the value of traditional mudbrick structures, which have survived to the present day with their spatial qualities and nature-friendly architectural features, in the context of their preservation and transmission to future generations. The method of the study will be evaluated in addition to the literature and field research on the design criteria, construction methods and construction methods of adobe/earth-based structures in the Elazığ region, as well as the importance of the implementation of conservation interventions at the building and settlement scale. The study aims to reveal the potential of preserving the spatial values of structures built with adobe-based building materials, which are located within traditional settlement areas with their unique characteristics, for the future through conservation interventions, as well as their contribution to ecology.

Özet Son yıllarda inşaat endüstrisi, yapı malzemelerinin üretimi ve kullanımında sarf edilen enerjinin yol açtığı küresel ısınma ve atık yönetimi gibi konuların ekolojiye olan zararları tüm dünyada ciddi tehditler yaratmıştır. Bu bağlamda ekolojiyi destekleyen ve çevre sorunlarını azaltan yenilenebilir enerji kaynakları ve malzemeleri her geçen gün daha büyük önem kazanmıştır. Buradan hareketle yapım endüstrisinde ekolojik malzeme kullanımı ve doğa dostu yapım sistemlerine yönelik pek çok bilimsel çalışma ve uygulamalar da gerçekleştirilmektedir. Son dönemde dikkat çeken çözüm değeriyle geleneksel mimari kriterleri, yapım teknikleri ve malzemelerine olan ilgi de bu nedenle artmıştır. Geleneksel mimarinin yapı malzemelerinden biri olan toprak esaslı kerpiç malzeme ve özgün yapım tekniği son dönemde ekolojik mimari alanında da oldukça dikkat çeken bir konu olmuştur. Toprak esaslı kerpiç malzemenin düşük enerji harcayarak üretimi, uygulama alanlarında çevre dostu yapım tekniklerine sahip oluşu yanında atık yönetimi ile kullanıcı konforunu destekleme özellikleri de mimarlık alanında daha dikkat çekici hale gelmiştir. Çalışma ile Elazığ kırsal/kentsel yerleşim alanlarındaki geleneksel mimarinin yapı / yerleşim ölçeğindeki koruma anlayışının ne derece rasyonalist olduğu konusundan referansla kerpiç yapıların korunma ve ekolojik kentsel gelişime sunacağı katkılara odaklanılmıştır. Bu anlamda çalışma, geleneksel yerleşim alanlarının özgün unsurları ve sosyo-kültürel değerleriyle; yapı ve yerleşim ölçeğinde sağlanacak koruma müdahaleleri ile geleceğe aktarılmasının önemine dikkat çekmeyi hedeflemektedir. Çalışma, mekânsal nitelikleri ve doğa dostu mimari özellikleriyle günümüze kadar ulaşabilmiş olan geleneksel kerpiç yapıların korunma ve gelecek kuşaklara aktarma bağlamındaki değeri ortaya konacaktır. Çalışmanın yöntemi, Elazığ bölgesindeki yerleşim alanındaki kerpiç/toprak esaslı yapıların tasarım kriterleri, yapım yöntemlerine ilişkin literatür ve saha araştırması yanında, koruma müdahaleleri hususunun yapı ve yerleşim ölçeğindeki uygulamalarının önemi de değerlendirilecektir. Çalışma, özgün nitelikleriyle geleneksel yerleşim alanları içinde yer alan kerpiç esaslı yapı malzemelerinin kullanıldığı yapıların mekânsal değerlerinin korunma müdahaleleriyle geleceğe kazandırılmasındaki potansiyeli yanında ekolojiye olan katkısını da gözler önüne sermeyi hedeflemektedir.
Elazığ Geleneksel Mimarisinde Kerpiç Malzemenin Önemi ve Korunumu Üzerine İrdeleme
Keywords: Sustainable Architecture; Sürdürülebilir Mimari